Low-Velocity Knee Dislocations in Obese and Morbidly Obese Patients. Issue 4 (2nd April 2015) - Vaidya, Rahul; Roth, Matthew; Nanavati, Dhiren; Prince, Matthew; Sethi, Anil
Background: Knee dislocations from minor trauma have been reported sparsely in the literature. The consensus is that these injuries tend not to be associated with neurovascular compromise. Purpose: To present a series of atraumatic knee dislocations in obese and morbidly obese patients and to compare operative versus conservative treatment. Study Design: Case series; Level of evidence, 4. Methods: This study included 19 patients (21 knees) who presented with knee dislocation from a low-velocity or ultra low–velocity incident. Charts, radiographs, and magnetic resonance images (MRIs) were reviewed, and patients were reviewed based on their latest follow-up. We included patients in our database from 2001 to 2011 and compared knees of patients who had ligament repair or reconstruction (9 total knees) verses nonoperative treatment (12 total knees). Range of motion, activity levels, and knee laxity information were collected as outcome measures to compare operative and nonoperative results. Results: The mean age at presentation was 30.3 years (range, 15-74 years), with 5 men and 14 women. The average body mass index (BMI) was 41.4 kg/m 2 (range, 30-64.4 kg/m 2 ), with an average follow-up of 31 months (range, 12-72 months). Five patients (27%) had a popliteal artery injury, and 7 (44.4%) had a peroneal nerve injury at presentation. Four had a vascular repair, 1 had an amputation, and 3 of 7 patients had return of peroneal nerve. Ligament reconstruction was performed on 9 individuals. The average operating time for ligament reconstruction was 183% of that with injury-matched normal-weight patients. Eight operative patients who complied with therapy had an average range of motion of 91.4° (range, 60°-110°). The nonoperative patients had an average range of motion of 60.45° (range, 0°-120°). Two of these patients later required a total knee arthroplasty (3 total knee arthroplasties overall). Conclusion: Knee dislocations from minor falls occur in obese patients and are often accompanied by neurovascular complications. While surgical reconstruction is more time consuming and more difficult than that in normal-weight individuals, it may be preferable to nonoperative treatment.